PREDIKSI KETERSEDIAAN AIR SEBUAH DAERAH ALIRAN SUNGAI MENGGUNAKAN PENDEKATAN MODEL RAINRUN - Imam Suprayogi; Manyuk Fauzi; Bochari -; Resty Agesti Handayani (Jurnal APTEK, 2012)
Dependable flow analysis is often difficult to predict, because influenced by natural phenomena and there are have variability of space and time. In analysis dependable flow especially the Sumatera region, usual model is used is Mock Model . However the level of reliability and accuracy have not been fully answered than the prediction of dependable flow. So it needs to be tested using a model that other rainfall-run off.The model approach used in this study is RainRun, that to predict dependable flow for applied on Sumatera region. Data is used to apply of RainRun model is Indragiri Basin for the years 1995 to 1999 are rainfall, climatological and measured discharge.The result study showed that the RainRun model to Indragiri Basin in calibration phase Root Mean Square Error (RMSE) value respectively 1,327% and verification obtained RMSE value respectively 2,811 %. Where as Mock watershed model for same Basin in calibration phase RMSE value 5,298% and the verification phase is obtained RMSE value 13,760 %. The results of comparative models RainRun and models Mock by using statistical parameter RMSE test RainRun models showed a lower error rate than the model of Mock.